Acceptance of organ xenotransplantation among Latin American immigrants resident in the United States. (15th July 2016) - Ríos, Antonio; López‐Navas, Ana Isabel; Martínez‐Alarcón, Laura; Ramis, Guillermo; Hernández, Antonio Miguel; Ayala, Marco Antonio; Garrido, Gregorio; Ramírez, Pablo; Parrilla, Pascual
Abstract: Background: Making xenotransplantation socially acceptable is the first step in working toward the promotion of this potential therapy option for providing transplant organs. Objective: To analyze the attitude toward xenotransplantation among the Latin American population resident in Florida (the USA), and to determine the variables affecting this attitude. Methods: A sample of Latin American residents in the state of Florida was randomized and stratified according to nationality, age, and sex (n = 1524). Attitude was assessed using a validated questionnaire (PCID—XenoTx Rios) which was self‐completed anonymously. Statistical analysis: descriptive analysis, Student's t ‐test, the chi‐square test, and a logistic regression analysis. Results: The questionnaire completion rate was 95% (n = 1450). If it was assumed that xenotransplanted organs functioned as well as human ones, 10% (n = 147) would be in favor, 73% (n = 1092) against, and 17% (n = 246) undecided. If the results were worse, only 2% (n = 35) would be in favor. This favorable attitude was related to country of origin (Honduras and Guatemala; P < 0.001); age (P < 0.001); sex (women; P < 0.001); marital status (married; P < 0.001); descendents (yes; P < 0.001); level of formal education (secondary education and university; P < 0.001); participation in voluntary prosocial activities (yes; P < 0.001); having spoken about donation and transplantation within the family (yes; P < 0.001); a partner's favorable attitude toward transplantation (P = 0.040); religion (catholic; P < 0.001); knowing the attitude of one's religion toward donation (yes; P < 0.001); previous experience of donation and/or transplantation (yes; P < 0.001); a belief that one might need a transplant in the future (yes; P < 0.001); and a favorable attitude toward human donation (yes; P < 0.001). The following were associated with attitude in the multivariate analysis: age (≥40 yrs; OR = 1.152); marital status (married; OR = 500); prosocial activities (yes, I participate in them; OR = 9.196. No, but I would like to; OR = 332.538); religion (catholic; OR = 2000); attitude toward deceased organ donation (in favor; OR = 2000); and previous experience of donation and/or transplantation (yes; OR = 500). Conclusions: The attitude of Latin Americans resident in Florida toward xenotransplantation is very negative, and is determined by many psychosocial factors, mainly related to their prior attitude toward the different kinds of human organ donation.